RELIGIOSITY AND ISLAMIC BRANDING ON THE PURCHASE OF MUSLIM FASHION IN SHOPEE THROUGH TRUST - Rabiana, Riska; Sudirman, Sudirman; Muin, Rahmawati (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to examine the influence of religiosity and Islamic branding on Muslim fashion purchasing decisions at Shopee marketplace in Makassar City, wherein trust serves as an intervening variable. The research type is quantitative with confirmatory research design. Data collection method employed in this study is through primary data collection obtained from 225 samples, using a purposive sampling technique. Data analysis technique used in this study is Structural Equation Model (SEM) with Partial Least Square (PLS) version 4.0 approach. This research uncovers that religiosity has a positive and significant effect on purchasing decisions. Correspondingly, Islamic branding also has a positive and significant effect on purchasing decisions. The mediating effect of trust strengthens the relationship between religiosity and purchasing decisions and has a positive and significant effect. In the same way, the mediating effect of trust strengthens the relationship between Islamic branding and purchasing decisions and has a positive and significant effect. The implications of this study suggest that people of Makassar City, especially Muslim women who use the Shopee application, are expected to consider the aspects of religiosity and trust in choosing Muslim fashion products so that they are in accordance with sharia values. Likewise, marketplaces and manufacturers are also advised to strengthen Islamic branding in order to increase consumer trust. Further research can consider other variables that influence Muslim fashion purchasing decisions in Shopee marketplace to provide more comprehensive insights.